Determination of auxine content of soft wood cutted `Marianna GF8/1' (Prunus cerasifera x P. munsoniana) by High Performance Liquid Chromatography during rooting period - Végvári, G.; László, H. (International Journal of Horticultural Science, 2004)
The content of different auxins of soft-wood cutted plum rootstock 'Marianna GF8/1' (Prunus cerasifera x P. munsoniana) was determined during the rooting period. The level of auxin-concentration (exogenous and endogenous) of basic and intemodal part of cuttings was determined by WATERS HPLC equipment every 7 days during rooting period. The lengths soft wood cuttings were app. 30 cm long. The basal part of shoots were treated with 2000 pg/g concentrated indole-butiryc acid in talcum powder. After treatment the cuttings were placed in propagation green-house under intermittent mist. The plant hormones were extracted by methanol the solution was cleaned by paper-filter, and further cleaned by centrifuge. The effluent was examined by reversed phase High Performance Liquid Chromatography, with WATERS 2487 dual detector at 220 am on Symmetry C18 4,6x 150 column. Recovery and reproducibility assessment indicates good accuracy and acceptable relative standard deviation (RSD) 5%. Linear responses (r20.997) for calibration curve was obtained with IAA, IPA and IBA standard in range, with a limit of quantification of 0.15 g•m1-1. The concentration of IAA, IPA and IBA in the basal part of cuttings were measured, during the rooting period. We proved the external IBA was taken up by the plants. In the plants were found the IBA, and the IAA concentration of IBA treated cuttings was higher, than the untreated one.